Status of proverbs and idioms in translation studies (Journal of Oriental Studies, 2017)
It’s very important for each translator to know the role of proverbsand sayings, and collocations in everyday life and in other social spheresof human life, and to determine how often they occur in the practice oftranslation. Quite often, they are faced with this topic in the translationpractice. Awareness about the areas of human activity in which proverbsand sayings, and idioms are particularly frequent, simplifies the work of aninterpreter.This article is written based on the research, which was conducted as asurvey among translators, and on its results in the form of diagrams.